Theoretical approach on two factorial design on residual curvature of bar straightening in cross-roll arrangements - Sanjib, Roy; Arun Kiran, Pal (Journal of Production Engineering, 2022)
Use of straight round bars is necessary in industries due to requirement of raw material as input for production of value-added products. Bars are often available in bent condition; hence straightening is a necessity before commercial use. Therefore, choosing a proper lot of straightened bars with acceptable level of residual curvature is a quality requirement. Use of statistical analysis by Factorial Design will help in decision making through appropriate Test Hypothesis for quality criterion of acceptable range of residual curvatures. This paper has made an attempt to look into the applicability of Factorial Design in bar straightening process.